FINANCIAL DEVELOPMENT AND INVESTMENT MARKET INTEGRATION - Vojinovič, Borut; E. Theodoropoulos, Theodore (Economic Annals, 2005)
Financial development is correlated with several underlying regulatory variables (such as indicators of investor protection, market transparency, variables for corporate governance growth and rules for capital market development), which are under the control of national legislators and EU directives. This paper provides estimates of the relationship between financial market development and corporate growth and assesses the impact of financial market integration on this relationship with reference to European Union (EU) countries. The regression results obtained using this panel support the hypothesis that financial development promotes growth, particularly in industries that are more financially dependent on external finance. For policy purposes, analyzing changes in these regulatory variables may be a more interesting exercise than analyzing integration of the financial systems themselves. Since assuming that EU countries will raise its regulatory and legal standards to the U.S. standards appears unrealistic, in this case we examine a scenario where EU countries raise their standards to the highest current EU standard.